Silver-catalyzed direct spirocyclization of alkynes with thiophenols: a simple and facile approach to 3-thioazaspiro[4, 5]trienones. Issue 103 (7th October 2015) - Cui, Huanhuan; Wei, Wei; Yang, Daoshan; Zhang, Jimei; Xu, Zhihong; Wen, Jiangwei; Wang, Hua
Abstract : A convenient and efficient silver-catalyzed direct oxidative spirocyclization of alkynes with thiophenols leading to 3-thioazaspiro[4, 5]trienones has been developed under air. Abstract : A new and convenient silver-catalyzed direct oxidative spirocyclization of alkynes with thiophenols is described. This methodology provides a simple and practical approach to various 3-thioazaspiro[4, 5]trienones in moderate to good yields with high atom efficiency and excellent functional group tolerance.